2014
DOI: 10.1007/s00270-014-0857-6
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Aspiration Thrombectomy for the Treatment of Arterial Thromboembolic Occlusions Following Percutaneous Transluminal Angioplasty

Abstract: PAT enables endovascular treatment of iatrogenic thromboembolic complications after PTA with good technical and early clinical results and minimal morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 14 publications
1
16
0
Order By: Relevance
“…Review of all identified patients was performed in detail by two radiologists with more than two and ten years of experience in interventional radiology. As reported before [7] 176 acute infrainguinal arterial occlusions had been treated with PAT/PAE in 158 patients in the mentioned time period. The mean age of these 158 patients (61 female, 39%) was 73 years (with an age range from 39 to 96 years).…”
Section: Patientsmentioning
confidence: 77%
See 1 more Smart Citation
“…Review of all identified patients was performed in detail by two radiologists with more than two and ten years of experience in interventional radiology. As reported before [7] 176 acute infrainguinal arterial occlusions had been treated with PAT/PAE in 158 patients in the mentioned time period. The mean age of these 158 patients (61 female, 39%) was 73 years (with an age range from 39 to 96 years).…”
Section: Patientsmentioning
confidence: 77%
“…Though the technique is applied for more than 30 years there are limited data on the technical and clinical success rate and the rate of complications for this kind of treatment [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of invasiveness, amputation rate, haemorrhagic complications and cost, PAT is a safe, rapid and effective technique for thrombus removal in patients with thromboembolic complications. Since Horvath et al [10] suggested that small emboli occurring during PTA can be aspirated using a catheter in 1978, several studies on the clinical outcomes of PAT have been reported, with a technical success rate ranging from 87.0% to 96% [1,4,11]. In the present study, the technical success rate for PAT was 95.7% (22/23), which was similar to previously reported rates, and a >90% patency and an mTIMI grade 3 flow were achieved in 87.0% thromboembolic vessels after PAT.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have reported the effectiveness of PAT for acute arterial thromboembolism during lower extremity EVR [4,7]; besides, no study has compared the clinical outcomes of patients who undergo PAT for thromboembolism during EVR and those who undergo EVR without thromboembolic complications. Furthermore, no study has analysed the lesion characteristics of patients with thromboembolic complications and the associated predictors in patients who undergo peripheral endovascular procedures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation